Young children's use of derived fact strategies for addition and subtraction - Dowker, Ann (Frontiers in Human Neuroscience, 2014)
44 children between 6;0 and 7;11 took part in a study of derived fact strategy use. They were assigned to addition and subtraction levels on the basis of calculation pretests. They were then given Dowker’s (1998) test of derived fact strategies in addition, involving strategies based on the Identity, Commutativity, Addend + 1,Addend −1, and addition/subtraction Inverse principles; and test of derived fact strategies in subtraction, involving strategies based on the Identity, Minuend +1, Minuend -1, Subtrahend +1, Subtrahend -1, Complement and addition/subtraction Inverse principles. The exact arithmetic problems given varied according to the child’s previously assessed calculation level and were selected to be just a little too difficult for the child to solve unaided. Children were given the answer to a problem and then asked to solve another problem that could be solved quickly by using this answer, together with the principle being assessed. The children also took the WISC Arithmetic subtest. Strategies differed greatly in difficulty, with Identity being the easiest, and the Inverse and Complement principles being most difficult. The Subtrahend + 1 and Subtrahend – 1 problems often elicited incorrect strategies based on an overextension of the principles of addition to subtraction. It was concluded that children may have difficulty with understanding and applying the relationships between addition and subtraction. Derived fact strategy use was significantly related to both calculation level and to WISC Arithmetic scaled score.